Discordance in management of adverse events associated with oral therapies in hormone receptor–positive breast cancer among health care providers and experts: Findings from an online decision support tool. Issue 28 (1st October 2022) - Rosenthal, Kristen M.; Brandt, Kelly G; Spring, Laura; Marti-Smith, Marissa; Quill, Timothy A.; O'Shaughnessy, Joyce
Abstract : 382 Background: Oral targeted therapies (OTTs) inhibiting CDK4/6, PI3K, and mTOR have established roles across multiple lines of therapy in patients with advanced hormone receptor–positive, HER2-negative breast cancer (HR+ BC). Abemaciclib, a CDK4/6 inhibitor (i), now also is approved in the adjuvant setting for eligible patients with early-stage HR+ BC. These OTTs are associated with various adverse events (AEs), such as cytopenias, diarrhea, hepatotoxicity, and rash. Optimal AE management is critical to promote patient adherence and achieve the best possible outcomes. Here we report an analysis of healthcare professional (HCP) management of AEs associated with OTTs in HR+ BC using an online decision support tool. Methods: The online tool was developed with 5 BC experts providing recommendations on the management of AEs associated with OTTs. Within the online tool, HCPs were prompted to input relevant patient case details through a series of predefined questions, including which OTT and type of AE the patient is experiencing, along with their management approach. Participants were then shown an expert recommendation based on the specific characteristics of that case and were asked if their management plan changed based on that recommendation. Results: Between September 2021 and April 2022, 557 cases were entered by 390 participants. Among 291 cases of patients currently receiving oral therapy, CDK4/6i therapy was most commonly selected (82%), followed by PI3Ki (11%) and mTORi (8%) therapy. The most common AE reported for CDK4/6i, PI3Ki, and mTORi therapy were cytopenias (56%), hyperglycemia (64%), and stomatitis (57%), respectively. With CDK4/6i, HCPs were discordant with expert recommendations for management of AEs reported in 44%, 39%, and 35% of entered cases with ribociclib, abemaciclib, and palbociclib, respectively. The greatest variance between HCP and expert recommendations were with management of VTE, hepatotoxicity, QT prolongation, and rash (Table). Among HCPs with discordant results from the experts, 50% changed their AE management plan after viewing the expert recommendation. Conclusions: These data suggest that HCPs may be challenged to optimally manage AEs related to OTTs in patients with HR+ BC. Use of an online tool may enhance HCP management of these AEs for patients with HR+ BC. A detailed analysis of the tool, including HCP planned management vs expert recommendations, will be presented.Discordance between HCP and expert recommendations for managing CDK4/6i AEs. AE Related to CDK4/6i Therapy Cases Entered, n Discordant, % Cytopenias 102 37 GI toxicity 35 31 Rash 11 45 Interstitial lung disease 11 27 VTE 6 83 Hepatotoxicity 6 67 Hepatobiliary 5 20 QT prolongation 4 50